The TPP and TTIP Trade Agreements: The International Negotiation Process - Ioana Gutu (CES Working Papers, 2016)
Free trade is one of the ultimate purposes of the free trade agreements currently negotiated over the world. Two of these trials are represented by the Trans-Pacific Partnership (TPP) and the Transatlantic Trade and Investment Partnership (TTIP). The common feature of these two trade deals is represented by the United States, a global actor that is making sure that it will be able to trade in best conditions on both of its geographical shores: on the Pacific and on The Atlantic. The negotiations are still ongoing, but results are expected on both sides. An important issue for the third parties, but not only, is represented by the secrecy of the negotiations undertaken and the lack of transparency shown by the negotiating Governments. If the agreements are concluded, a major global impact on trade and investments is expected, with significant positive implications for the TPP and TTIP negotiating states.
Keywords: F01; 330; TTIP; TPP; EU; US; international negotiations